Caspase‐dependent cleavage of the mono‐ADP‐ribosyltransferase ARTD10 interferes with its pro‐apoptotic function. (13th February 2013) - Herzog, Nicolas; Hartkamp, Jörg D. H.; Verheugd, Patricia; Treude, Fabian; Forst, Alexandra H.; Feijs, Karla L. H.; Lippok, Barbara E.; Kremmer, Elisabeth; Kleine, Henning; Lüscher, Bernhard
<x xml:space="preserve">Abstract</x> ADP‐ribosylation is a post‐translational modification that regulates various physiological processes, including DNA damage repair, gene transcription and signal transduction. Intracellular ADP‐ribosyltransferases (ARTDs or PARPs) modify their substrates either by poly‐ or mono‐ADP‐ribosylation. Previously we identified ARTD10 (formerly PARP10) as a mono‐ADP‐ribosyltransferase, and observed that exogenous ARTD10 but not ARTD10‐G888W, a catalytically inactive mutant, interferes with cell proliferation. To expand on this observation, we established cell lines with inducible ARTD10 or ARTD10‐G888W. Consistent with our previous findings, induction of the wild‐type protein but not the mutant inhibited cell proliferation, primarily by inducing apoptosis. During apoptosis, ARTD10 itself was targeted by caspases. We mapped the major cleavage site at EIAMD406↓S, a sequence that was preferentially recognized by caspase–6. Caspase‐dependent cleavage inhibited the pro‐apoptotic activity of ARTD10, as ARTD10(1–406) and ARTD10(407–1025), either alone or together, were unable to induce apoptosis, despite catalytic activity of the latter. Deletion of the N–terminal RNA recognition motif in ARTD10(257–1025) also resulted in loss of pro‐apoptotic activity. Thus our findings indicate that the RNA recognition motif contributes to the pro‐apoptotic effect, together with the catalytic domain. We suggest that these two domains must be physically linked to stimulate apoptosis, possibly targeting ARTD10 through the RNA recognition motif to specific substrates that control cell death. Moreover, we established that knockdown of ARTD10 reduced apoptosis in response to DNA‐damaging agents. Together, these findings indicate that ARTD10 is involved in the regulation of apoptosis, and that, once apoptosis is activated, ARTD10 is cleaved as part of negative feedback regulation. Structured digital abstract Caspase-8 cleaves ARTD10 by protease assay (View interaction) Caspase-6 cleaves ARTD10 by protease assay (View interaction)